Associations between subjective and objective measures of stress and load: an insight from 45-week prospective study in 189 elite athletes - Drole, Kristina; Doupona, Mojca; Steffen, Kathrin; Jerin, Aleš; Paravlic, Armin (Frontiers in Psychology, 2025)
IntroductionThe aim of this study was to investigate the associations between subjective and objective measures of stress and load in elite male handball players at both the group and individual levels.MethodsIn this 45-week prospective cohort study, 189 elite male handball players weekly reported their perceived stress and load across training, competition, academic, and work domains. Blood samples were collected five times during the 2022/23 season to measure cortisol and the free testosterone to cortisol ratio (FTCR). We derived a “load” variable as the sum of training, competition, academic and work hours and calculated acute, chronic, and acute-to-chronic ratio variables for both load and stress. Associations between subjective and objective measures were analyzed using Spearman’s rank correlation.ResultsWeak to moderate positive associations were found between load and perceived stress (r = 0.19 to 0.46, p < 0.001), and between perceived stress and cortisol (r = 0.10, p = 0.023). Weak negative associations were found between perceived stress and FTCR (r = −0.18 to −0.20, p < 0.001) and between load and FTCR (r = −0.13, p = 0.003). A total of 86% of athletes had positive associations between stress and load (47% weak, 34% moderate, 5% high); 78% between stress and cortisol (27% weak, 22% moderate, 29% high); and 63% demonstrated negative associations between FTCR and load (18% weak, 32% moderate, 13% high).ConclusionThis study highlights the complexity between subjective and objective measures of stress and load in athletes. Understanding the link between these measures may help coaches and sports scientists streamline athlete monitoring. In cases where moderate to strong associations exist, subjective measures might serve as a reliable substitute for objective ones, making the monitoring process more time- and cost-efficient.